Compound Homojunction:Heterojunction Reduces Bulk and Interface Recombination in ZnO Photoanodes for Water Splitting. Issue 10 (5th January 2017) - Wang, Ning; Liu, Min; Tan, Hairen; Liang, Junhui; Zhang, Qixing; Wei, Changchun; Zhao, Ying; Sargent, Edward H.; Zhang, Xiaodan
Abstract : Photoelectrochemical water splitting is far more efficient thanks to the novel ZnOSe/ZnO/BZO thin‐film photoanodes fabricated in this work. A novel structure is developed for simultaneously suppressing the charge recombination in the ZnO bulk and at the semiconductor–electrolyte interface. This structure achieves a five‐fold enhancement in water‐splitting performance, compared to that of pristine ZnO photoanodes, when illuminated using visible light.